Analisis Kesulitan Guru Matematika dalam Menerapkan Pendekatan Saintifik berdasarkan Kurikulum Merdeka di SMP - Fatimah, Fatimah; Suaedy, Nurdyanti (YASIN, 2025)
Teachers' difficulties in applying the scientific approach integrated with the Kurikulum Merdeka, particularly in junior high school mathematics instruction, constitute the central concern of this study. The research focuses on obtaining in-depth insights into the challenges faced by mathematics teachers at SMP Negeri 1 Sungguminasa, Gowa Regency. A qualitative approach was employed, involving two mathematics teachers as participants. The primary instrument was the researcher, supported by instructional module review sheets, classroom observation forms, and interview guides. The findings reveal that teachers face several challenges, including translating Learning Outcomes (Capaian Pembelajaran) into specific learning indicators, contextualizing mathematical content with developments in science and technology, managing classrooms effectively, providing varied learning media, motivating students to ask questions, facilitating access to learning resources, and delivering comprehensive content analysis and explanation. Teachers also reported difficulties in demonstrating abstract concepts, facilitating experiential observation-based activities, and guiding students to present their learning outcomes both orally and in written form. While both teachers demonstrated adequate readiness in lesson planning, they still require technical support—one in breaking down the Learning Objectives Sequence (Alur Tujuan Pembelajaran, ATP) into measurable indicators (Subject 1), and the other in developing student worksheets (Lembar Kerja Peserta Didik, LKPD) (Subject 2). The study concludes that continuous professional development and institutional support are essential to ensure a more effective and contextually relevant implementation of the Kurikulum Merdeka in mathematics education.